(untitled) (Pesquisa Odontológica Brasileira, 2000)
The study was designed both to evaluate the frequency of bacteremia following teeth extraction and to identify the microorganisms isolated in post-extraction bacteremia. In addition, the antibiotic susceptibility of the microorganisms was tested. For this, 26 patients were divided into two groups according to the treatment they had received: 1) clorhexidine (0.12%) mouthwash followed by rubbing the teeth surfaces using the same solution; 2) two mouthrinses with 15 ml of cetylpyridinium chloride for one minute, interposed by rubbing the teeth surfaces with hydrogen peroxide (3%). Regardless of the utilized antisepsis method, the frequency of post-extraction bacteremia was high. Anaerobic microorganisms were predominant in post-extraction bloodcultures, presenting susceptibility to amoxicillin and to chloramphenicol.